PENGARUH CHARCTER STRENGTH TERHADAP KEBAHAGIAAN DI TEMPAT KERJA PADA KARYAWAN SALES - Bastian, Bayu; Simatupang, Marhisar; Greata, Holy (unprimdn.ac.id, 2023)
The purpose of this study was to determine the effect of character strength on happiness at work for sales employees at PT. Matahari Department Store Festive Walk Karawang. In this study there are two variables, namely character strength and happiness at work. The hypothesis of this study is that there is an effect of character strength on happiness at work for sales employees at PT. Matahari Department Store Festive Walk Karawang. The number of samples used was 70 sales employees at PT. Matahari Department Store Festive Walk Karawang. Using saturated sampling research method. The data method in this study uses quantitative research methods. The reliability of this research shows that the results of character strength are 0.941 and happiness at work is 0.799, so both variables are declared to have a reliable value. The analysis in this study uses a simple regression analysis using SPSS 22.0. Based on the results of the hypothesis test, it is known that the variable character strength on happiness at work has a significant effect with a value of 0.012 less than 0.5. The results showed that there was an effect of character strength on happiness at work for sales employees at PT. Matahari Department Store Festive Walk Karawang.